iPad 2 how cutting-edge apps bring new hardware to life!. - Bookwalter, J. R. (Mac life)
These days the iPad2 is teh prettiest gadget at the ball, and the hype focuses on its shiny upgrades - like the dual cameras, gyroscope, and the dual processor. But in truth, none of that matters without the cutting-edge apps that put that tech to good use. Whether you're using the iPad 's cameras to organize receipts or you're melting faces with GarageBand, our expert advice and app picks will help you get the most out of your iPad 2.